The Evaluation of Fuzzy-Linear and Non- Linear - Mrs. Seema Rani, Seema (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The linear and non-linear fuzzy systems are modified with examples of some fuzzy solutions by the application of fuzzy sets, arithmetic solutions, and other major formulas. In this topic, the ongoing topic will discuss fuzzy equations, where linear and non-linear portions are equally discussed. Even the non-linear equation is constructing the process of co-efficient of the corresponding fuzzy solution. Here define the unbiased connection between the linear and non-linear equation with Fuzzy sets of problems and some specific examples. Also, dictation the fuzzy appropriate solution on general theory. The upper limit of the model rule and numerical variables structure for practical method. Lastly, the Fuzzy methods are the most perfect estimated mathematical characteristic for both applied and pure mathematics.